Perceived Academic Stress and Depression: The Mediation Role of Mobile Phone Addiction and Sleep Quality - Zhang, Xin; Gao, Fei; Kang, Zheng; Zhou, Hongguo; Zhang, Jianfeng; Li, Jingjing; Yan, Jun; Wang, Jiahui; Liu, Huan; Wu, Qunhong; Liu, Baohua (Frontiers in Public Health, 2022)
Background: Although academic stress is a well-known risk factor for students’ depression, little is known about the possible psychological mechanisms underlying this association. In this study, we investigated the prevalence of depression and sleep disturbance among Chinese students, examined the relationship between perceived academic stress and depression, considered if mobile phone addiction and sleep quality is a mediator of this relationship, and tested if mobile phone addiction and sleep quality together play a serial mediating role in the influence of perceived academic stress on depression. Method: A cross-sectional survey was conducted among students from September to December 2018 in Heilongjiang Province, China. The final analysis included 5,109 students. Mobile phone addiction, sleep quality, and depressive symptoms were assessed using the Mobile Phone Addiction Index, Pittsburgh Sleep Quality Index, and Center for Epidemiologic Studies-Depression scales, respectively. The serial mediation model was used to analyze the relationship between perceived academic stress, mobile phone addiction, sleep quality, and depression. Results: Among all participants, the prevalence of depressive symptoms and sleep disturbance was 28.69% and 27.95%, respectively. High school students showed the highest scores of perceived academic stress (2.68 ± 1.06), and the highest prevalence of depressive symptoms (33.14%) and sleep disturbance (36.47%). The serial mediation model indicated that perceived academic stress was a significant predictor of depression (B = 0.10, SE = 0.02, 95% CI = 0.06 – 0.13). Additionally, mobile phone addiction (B = 0.08, 95% boot CI = 0.06 – 0.11) and sleep quality (B = 0.27, 95% boot CI = 0.22 – 0.33) played a mediating role between perceived academic stress and depression. Mobile phone addiction and sleep quality together played a serial mediating role in the influence of perceived academic stress on depression (B = 0.11, 95% boot CI = 0.08 – 0.14). Furthermore, the indirect effect (i.e., the mediating effect of mobile phone addiction and sleep quality) was significant and accounted for 64.01% of the total effect. Conclusions: Our research results underscore the need for stakeholders—including family members, educators, and policy makers—to take preventative intervention measures to address depression among Chinese students, especially high school students.